CARBON NANOTUBE TRANSMITTER-RECEIVER SYSTEM FOR HYDROCARBON EXPLORATION - Ahmad Badnizzaman B Ahmad Sallehim, Ahmad Badnizzaman (Universiti Teknologi Petronas, 2010)
The main objective of this project is the development of transmitter-receiver prototype. The design is based on Horizontal Electric Dipole (HED) which consist an electric field and the magnetic field which are perpendicularly to each other. The parameters that will be taking into account in designing the antenna and detector are the material, frequency, length and diameter of the antenna. Simulations and experiments have been conducted to study the effect of material, length, diameter and frequency in resulting magnetic field and electric field of the antenna.